Selected papers from Dependently Typed Programming 2010 – Overview. (27th November 2014) - ALTENKIRCH, THORSTEN; MCBRIDE, CONOR
Abstract : This special issue comprises selected papers which were presented at the workshop on dependently typed programming (DTP 10) in Edinburgh in July 2010 – affiliated with Federated Logic conferences (FLOC 10). Earlier workshops on dependently typed programming took place in Nottingham in 2008 (DTP 2008) and there also has been a Dagstuhl seminar (04381) on this subject in 2004. After DTP 2010, in 2011 a workshop on dependently typed programming (DTP 11) took place in Nijmegen affiliated with Interactive Theorem Proving 2011 (ITP 11). In September 2011 there also was a DTP workshop in Shonan, Japan.